Peculiarities of thermal expansion of quasi-two-dimensional organic conductor κ-(BEDT–TTF)2Cu[N(CN)2]Cl - Dolbin, A.V.; Khlistuck, M.V.; Eselson, V.B.; Gavrilko, V.G.; Vinnikov, N.A.; Basnukaeva, R.M.; Danchuk, V.V.; Konstantinov, V.A.; Nakazawa, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Linear coefficient of thermal expansion α(Т) of single crystal (BEDT–TTF)2Cu[N(CN)2]C1 was studied along the crystal layers using the method of precise capacitive dilatometry in the temperature range 2–285 K. It is positive in this direction over the entire temperature range. Anomalies of thermal expansion were observed at 29–30 K and 74–80 K. The anomaly near 30 K is, apparently, due to the transition between the paramagnetic phase and the antiferromagnetic insulator state. Peak of α(Т) at 78 K corresponds to a phase transition related to orientational disordering of ethylene groups in dimers of BEDT–TTF. A broad maximum of α(Т) in the temperature range 40–70 K, is apparently explained by fluctuations of charge within the dimers, and by spin fluctuations, which first increase with increasing temperature, and then decrease in process of thermal disordering of dimers.